Burn Severity in Canada's Mountain National Parks: Patterns, Drivers, and Predictions - Weiwei Wang; Xianli Wang; Wanli Wu; Futao Guo; Jane Park; Guangyu Wang (Geophysical Research Letters)
Abstract Fine‐scale estimation of burn severity in the Canadian Rocky Mountain region with mixed‐severity fires is of substantial implications but still lacking. We investigated satellite‐derived burn severity from 1985 to 2015 at 30‐m resolution in three mountain national parks in Canada: Banff, Kootenay, and Yoho National Parks. Results show that fuel type had the most significant influence on burn severity, whereas the three groups of continuous variables (topography, vegetation, and climate) contributed equally to the model, indicating the complex mechanism of environmental controls on fire behavior in this heterogeneous mountain region. The predicted burn severity potentials of the whole parks in 2002 and 2012 showed overall consistent spatial patterns, and lightning‐caused fires produced more high‐severity burn areas than prescribed fires. Generally, local communities in the intensive fire management zone were predicted to have relatively low burn severity, reflecting the fire management effectiveness.